Coupling of Anammox Activity and PAH Biodegradation: Current Insights and Future Directions - Francesco Bianco, Francesco Bianco; Adel Ali Saeed Al-Gheethi, Adel Ali Saeed Al-Gheethi; Marco Race, Marco Race (Mdpi, 2023)
Anaerobic ammonium oxidation (anammox) has shown success in past years for the treatment of municipal and industrial wastewater containing inorganic nutrients (i.e., nitrogen). However, the increase in polycyclic aromatic hydrocarbon (PAH)-contaminated matrices calls for new strategies for efficient and environmentally sustainable remediation. Therefore, the present review examined the literature on the connection between the anammox process and PAHs using VOSviewer to shed light on the mechanisms involved during PAH biodegradation and the key factors affecting anammox bacteria. The scientific literature thoroughly discussed here shows that PAHs can be involved in nitrogen removal by acting as electron donors, and their presence does not adversely affect the anammox bacteria. Anammox activity can be improved by regulating the operating parameters (e.g., organic load, dissolved oxygen, carbon-to-nitrogen ratio) and external supplementation (i.e., calcium nitrate) that promote changes in the microbial community (e.g., Candidatus Jettenia), favoring PAH degradation. The onset of a synergistic dissimilatory nitrate reduction to ammonium and partial denitrification can be beneficial for PAH and nitrogen removal